2018
DOI: 10.1080/00015385.2018.1475027
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized trials on percutaneous patent foramen ovale closure for prevention of migraine

Abstract: PFO closure might be beneficial in migraine patients by reducing migraine attacks and migraine days, especially in patients whose majority of migraine attacks are with aura. However, those benefits were not associated with an improvement in responders' rate or complete resolution of migraine; raising concerns on the magnitude of clinical benefit of PFO closure in migraine prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
5
18
0
1
Order By: Relevance
“…In our analysis, we have also found a significant improvement in the reduction in migraine attacks and migraine days per month associated with PFO closure. Elbadawi et al conducted a meta-analysis of the 3 RCTs and concluded that PFO closure might be beneficial in migraine patients by reducing migraine attacks and migraine days, especially in patients whose majority of migraine attacks were with aura [27]. Our analysis reached a consensus with their conclusion.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In our analysis, we have also found a significant improvement in the reduction in migraine attacks and migraine days per month associated with PFO closure. Elbadawi et al conducted a meta-analysis of the 3 RCTs and concluded that PFO closure might be beneficial in migraine patients by reducing migraine attacks and migraine days, especially in patients whose majority of migraine attacks were with aura [27]. Our analysis reached a consensus with their conclusion.…”
Section: Discussionmentioning
confidence: 57%
“…Schwerzmann et al found that headache attacks in patients with migraine were reduced by >50%, whereas no reduction was observed in patients with nonmigraine headaches, which render a sole placebo effect unlikely [21]. By the same token, Elbadawi et al conducted a sensitivity analysis including only sham-controlled studies in the 3 RCTs' meta-analysis, and results also showed improvement of primary outcome with PFO closure [27], which support that the effect is unlikely to be caused just by a placebo effect. Similarly, it should not be ignored that the control group may also have placebo effects on patients due to sham procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The PREMIUM trial did not achieve a> 50% reduction in number of monthly migraine attacks, but the subgroup with frequent aura demonstrated both improved responder rate and cessation rate. A meta‐analysis of the 3 trials found a decrease in mean monthly migraine attacks and migraine days, suggesting possible benefit of percutaneous closure 185 . A 2020 retrospective, single‐center study of 474 patients who underwent transcatheter PFO closure for cryptogenic stroke had a considerably longer follow‐up (median 3.2 years) than any of the 3 RCTs 159 .…”
Section: Mechanistic Implications Of Clinical Trialsmentioning
confidence: 99%
“…71 A meta-analysis of trials examining the effects of PFO closure in migraineurs concluded that the procedure may be beneficial in patients whose predominant migraine type includes aura. 72 However, a subsequent randomized controlled trial of 230 patients failed to reach the primary end point of a 50% reduction of migraine attacks after PFO closure. 73…”
Section: Managing the Comorbidities Of Migraine With Auramentioning
confidence: 99%